Uma Roda de Choro no piano: práticas idiomáticas de performance de gravações dos pianistas Cristovão Bastos e Laércio de Freitas - Luísa Camargo Mitre de Oliveira (2017)
The present research deals with aspects of choro practice at the piano, focusing on idiomatic elements of the instrument, mainly in the context of collective performance. Elements of performances recorded in audio and video of Cristóvão Bastos and Laércio de Freitas, two important Brazilian pianists of the genre, were analyzed, with a primary focus on the piano integrated in groups of varied instrumental formations. To aid in the visualization and interpretation of these elements, the process of descriptive transcription (considered, in the present work, as the recording of musical sounds through traditional musical notation) was utilized. To consider questions about the material analyzed and others raised during the research process, pianists working in the current musical scene of choro were interviewed, excerpts of which are included in the text.